Kinetic and thermodynamic studies of the adsorption of heavy metals on to a new adsorbent: coal mine drainage sludge - Cui, M.; Jang, M.; Cho, S.H.; Khim, J. (2010)
In this study, we investigated the application of sludge waste obtained from a coal mine drainage treatment facility that treats acid mine drainage (designated as AMD) from metal-mine water. The coal mine drainage sludge (designated as CMDS), which contained 70 goethite and 30 calcite, was utilized as a sorption material for Cu(II) and Zn(II) removal from an aqueous solution of metallic mine drainage. The equilibriums and kinetics were investigated during a series of batch adsorption experiments. The Langmuir model was used to fit the equilibrium data, resulting in the best fits. The removal efficiencies were controlled by solution pH, temperature, initial concentration of heavy metal, sorbent amount and contact time. The pseudo-second-order kinetic model was used to fit the kinetic data, providing a good correlation with the experimental data. The results of a thermodynamic study showed that the activation energies (EA) were 3.75 and 1.75 kJ mol-1 for the adsorption of Cu(II) and Zn(II) on to CMDS at pH 5.5. These values of activation energy could correspond to physisorption. The positive values obtained for both the standard enthalpy change, Î0, and the standard entropy change, ÎS0, suggest that the adsorption of Cu(II) and Zn(II) on to the CMDS was an endothermic reaction and that randomness increased at the solid-liquid interface during the adsorption of Cu(II) and Zn(II) on to the CMDS. The adsorption process also followed a pseudo-second-order kinetic model. Â© 2010 Taylor & Francis.